Cooperative learning in the efl learning process of young learners - Miranda Salazar, María Soledad (2007)
1. The learning process. 2. Implementing cooperative learning. 3. Presentation and analysis of the results of the data regarding cooperative learning in the efl learning process of young learners. 4. Conclusions and recommendations